Genome-wide transcriptome profiling revealed biological macromolecules respond to low temperature stress in Brassica napus L - Hussain, Muhammad Azhar; Luo, Dan; Zeng, Liu; Ding, Xiaoyu; Cheng, Yong; Zou, Xiling; Lv, Yan; Lu, Guangyuan (Frontiers in Plant Science, 2022)
Brassica napus L. (B. napus) is a vital oilseed crop cultivated worldwide; low temperature (LT) is one of the major stress factors that limit its growth, development, distribution, and production. Even though processes have been developed to characterize LT-responsive genes, only limited studies have exploited the molecular response mechanisms in B. napus. Here the transcriptome data of an elite B. napus variety with LT adaptability was acquired and applied to investigate the gene expression profiles of B. napus in response to LT stress. The bioinformatics study revealed a total of 79,061 unigenes, of which 3,703 genes were differentially expressed genes (DEGs), with 2,129 upregulated and 1,574 downregulated. The Gene Ontology and Kyoto Encyclopedia of Genes and Genomes enrichment analysis pinpointed that the DEGs were enriched in LT-stress-responsive biological functions and metabolic pathways, which included sugar metabolism, antioxidant defense system, plant hormone signal transduction, and photosynthesis. Moreover, a group of LT-stress-responsive transcription factors with divergent expression patterns under LT was summarized. A combined protein interaction suggested that a complex interconnected regulatory network existed in all detected pathways. RNA-seq data was verified using real-time quantitative polymerase chain reaction analysis. Based on these findings, we presented a hypothesis model illustrating valuable information for understanding the LT response mechanisms in B. napus.